Upaya Meningkatkan Hasil Belajar Siswa Pada Pelajaran Matematika Materi Pecahan Melalui Metode Demonstrasi - Simanjuntak, Haholongan; Kirana, Desi Irawati (JURNAL MATHEMATIC PAEDAGOGIC, 2024)
The aim of this research is to improve students' mathematics learning outcomes in fraction material through the demonstration method. This type of research is Classroom Action Research (PTK). The subjects of this research were 30 class II students at SD N Cipari, Klapanunggal District. The evaluation test on learning outcomes on fraction material was used as a research instrument. Observation and tests are data collection techniques. The results of the pre-test carried out during the pre-cycle averaged 66 and the percentage of learning completion was only 43.33%. The results of research in cycle 1 showed an increase from an average of 66 to 77.33 with a learning completion percentage of 60%. In cycle II there was also an increase in scores from an average of 77.33 to 86 with the percentage of student learning completion being 93.33%. From the results of the explanation above, this classroom action research was successful. The results of the research concluded that the demonstration method in mathematics learning could increase understanding of the sub-material of fractions which had an impact on increasing the minimum completeness criteria for class II students at SD N Cipari, Klapanunggal District